Caesarean delivery is associated with higher risk of overweight in the offspring: within-family analysis in the SUN cohort. Issue 7 (24th April 2020) - Martín-Calvo, Nerea; Martínez-González, Miguel Ángel; Segura, Gloria; Chavarro, Jorge E; Carlos, Silvia; Gea, Alfredo
Abstract : Background: Most studies assessing the association between caesarean delivery (CD) and childhood overweight/obesity have failed to account for important confounders, such as maternal prepregnancy body mass index (BMI) or the indication of the CD. Furthermore, within-family analyses have reported contradictory results. We aimed at evaluating the association between CD and offspring's risk of overweight/obesity while adjusting for important confounders and accounting for correlations between siblings. Methods: Women in the 'Seguimiento Universidad de Navarra' cohort provided structured information regarding their pregnancy history and their children's health through online cross-sectional questionnaires. We calculated adjusted differences in BMI z-score and risk ratios (RR) for offspring's overweight/obesity associated with CD, with hierarchical models to account for correlations between siblings. We also performed a within-family analysis in 341 siblings who were discordant in delivery mode, using conditional multivariable logistic regression. Results: Among the 2791 children analysed, those born by CD had higher average BMI z-scores (difference: 0.17; 95% CI 0.07 to 0.27) and higher risk of overweight/obesity (RR: 1.32, 95% CI 1.05 to 1.65) than children born vaginally. The association did not differ by maternal characteristics or offspring's age strata, and the results were consistent in sensitivity analyses. Furthermore, within-family analysis showed that children born by CD had 2.67-fold higher risk of overweight/obesity (95% CI 1.10 to 5.12) than their peers born vaginally. Conclusion: Children born by CD have higher average BMI z-scores and higher risk of overweight/obesity than children born vaginally. The consistency of these findings across multiple approaches to address potential residual confounding likely suggests a true biological effect.